Pavement life cycle oriented to its cracking and maintenance - Huamán Contreras, Anais Klelia Yadira (2023)
The achievements obtained after the systematic review carried out are shown, in which the characteristics of the studies of the life phases of pavements focused on cracking and care will be identified, and the consensus reached. To achieve this, the Redalyc, Web of Science, Scopus and Scielo databases were reviewed, which resulted in 10 articles that covered the criteria of the subject. Theoretically, most of the works use the rule-based theory. In order to fully understand and address the problems of roof cracks and maintenance-oriented life cycle, it is recommended to develop studies using various samples and a database, where a review procedure is carried out to verify the basic information according to the subject. And as for the assessment, it is given according to national and international research sources where they are compared on certain variables and factors to be considered. Sidewalks play a key role in road infrastructure because they provide a walking surface for vehicles and pedestrians. However, over time, pavement is exposed to various weather conditions, traffic loads, and other factors that can cause cracking and damage. Therefore, it is vital to understand the lifetime of the pavement and implement effective maintenance strategies to extend its useful life and guarantee its functionality. This article examines pavement and its useful life, focusing on cracking and proper maintenance.